Formation of AAV single stranded DNA genome from a circular plasmid in Saccharomyces cerevisiae. - Tiziana Cervelli; Ana Backovic; Alvaro Galli (PLoS ONE)
Adeno-associated virus (AAV)-based vectors are promising tools for targeted transfer in gene therapy studies. Many efforts have been accomplished to improve production and purification methods. We thought to develop a simple eukaryotic system allowing AAV replication which could provide an excellent opportunity for studying AAV biology and, more importantly, for AAV vector production. It has been shown that yeast Saccharomyces cerevisiae is able to replicate and form the capsid of many viruses. We investigated the ability of the yeast Saccharomyces cerevisiae to carry out the replication of a recombinant AAV (rAAV). When a plasmid containing a rAAV genome in which the cap gene was replaced with the S. cerevisiae URA3 gene, was co-transformed in yeast with a plasmid expressing Rep68, a significant number of URA3(+) clones were scored (more than 30-fold over controls). Molecular analysis of low molecular weight DNA by Southern blotting revealed that single stranded DNA is formed and that the plasmid is entirely replicated. The ssDNA contains the ITRs, URA3 gene and also vector sequences suggesting the presence of two distinct molecules. Its formation was dependent on Rep68 expression and ITR. These data indicate that DNA is not obtained by the canonical AAV replication pathway.